2007
DOI: 10.1186/1476-511x-6-19
|View full text |Cite
|
Sign up to set email alerts
|

ApolipoproteinA1-75 G/A (M1-) polymorphism and Lipoprotein(a); Anti- vs. Pro-Atherogenic properties

Abstract: Background: ApolipoproteinA1(apoA1) is the major apoprotein constituent of high-densitylipoprotein(HDL). The relationship of apoA1 -75 bp(M1 -) allele polymorphism with lipoprotein phenotype and cardiovascular diseae (CVD) remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…Aggregation of apoA‐I to Lp(a) is thus well possible during pro‐oxidative state. An association of significantly higher Lp(a) levels with the MI‐(G/A) allele of the apoA‐I‐75 bp polymorphism has been reported in Omani people irrespective of gender and diabetes .…”
Section: Discussionmentioning
confidence: 94%
“…Aggregation of apoA‐I to Lp(a) is thus well possible during pro‐oxidative state. An association of significantly higher Lp(a) levels with the MI‐(G/A) allele of the apoA‐I‐75 bp polymorphism has been reported in Omani people irrespective of gender and diabetes .…”
Section: Discussionmentioning
confidence: 94%
“…У женщин-носителей А аллеля была обнаружена взаимосвязь между генотипом и диетой, зависящая от АпоА1 G-A полиморфизма: повышенное потребление полиненасыщенных жирных кислот ассоциировалось с повышением концентрации ЛВП у женщин с А-аллелью, тогда как у женщин с G/G генотипом наблюдался противоположный эффект. В некоторых исследованиях было обнаружено, что носительство А-аллели (М1-) в промотерном регионе гена апоАI ассоциируется с достоверным повышением концентрации ЛП (а), независимо от пола и наличия СД [9,10]. Также в некоторых экспериментальных исследованиях было показано, что А аллель связана со снижением транскрипции апоА1, который, как известно, имеет антиатерогенное значение.…”
Section: Discussionunclassified
“…In women, carriers of the A allele was found the relationship between genotype and diet, depending on Apo AI GA polymorphism: increased intake of polyunsaturated fatty acids was associated with an increased concentration of HDL, whereas in women with G / G genotype was observed adverse effect (Ordovas, 1999). In some studies it was found that carriers of the A allele (M1) in the promoter region of Apo AI gene is associated with a significant increase in the concentration of lipoprotein (a), regardless of gender and the presence of diabetes (Albahrani et al, 2007;Heng et al, 2001). Also, in some experimental studies have shown that the A allele is associated with reduced transcription of lipoprotein AI, which is known to have important antiatherogenic value (Matsunaga et al, 1999;Smith et al, 1992;Tuteja et al, 1992).…”
Section: Discussionmentioning
confidence: 99%